The Fiscal Capacity of The Seven New Provinces and its Implications - Saragih, Juli Panglima (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
Since 2001 the regional autonomy policies have brought out seven new provinces in Indonesia. Consequently, they require the central transfer budget to finance the delegated duties and authorities and the development programs in each province. Since its establishment until today, the fiscal capacity in seven provinces except Banten has not fulfilled the increase in local expenditure needs every year. It still much depends on the central transfer because the local revenue source like PAD is very low. This research uses a descriptive method-analysis by analyzing the secondary data relevant to the discussed topic and using the concept of fiscal capacity in the framework of the fiscal decentralization theory. The results of this qualitative research explain that the high fiscal capacity index (IKF) is obtained by four provinces those are Bangka Belitung, West Papua, Riau, and North Maluku, while the intermediate index is obtained by Banten, and the low fiscal capacity index is obtained by Gorontalo and West Sulawesi. Good fiscal capacity with high index does not guarantee that the poor population in the area will be reduced as West Papua and Riau which populations are still relatively large. Besides, Bantam with the very high PAD compared with six other provinces still has a large number of poor population of poor among seven provinces. But, overall the central transfer is recognized to be very helpful for the fiscal capacity of the seven new provinces above.